2002
DOI: 10.4141/a01-041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary conjugated linoleic acid on some aspecific immune parameters and acute phase protein in weaned piglets

Abstract: Corino, C., Bontempo V. and Sciannimanico D. 2002. Effects of dietary conjugated linoleic acid on some aspecific immune parameters, and acute phase protein in weaned piglets. Can. J. Anim. Sci. 82: 115-117. The aim of this study was to determine the influence of dietary supplementation of conjugated linoleic acid (CLA) on some immune system parameters in piglets. Forty-two weaned piglets, 12.44 ± 1.96 kg liveweight, were fed diets containing 1% sunflower oil (control, C), 0.5% CLA plus 0.5% sunflower oil (T1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…Sugano et al (1998) reported that CLA increased the production of non-specific immunoglobulins such as IgA, IgG, and IgM and decreased IgE concentration in rats. Corino et al (2002) also observed an increase in serum IgG of piglets Effects of dietary CLA supplementation on weaned pigs 49 due to dietary CLA supplementation. These studies indicated that CLA had positive modulatory impact on the humoral immune response.…”
Section: Discussionmentioning
confidence: 73%
“…Sugano et al (1998) reported that CLA increased the production of non-specific immunoglobulins such as IgA, IgG, and IgM and decreased IgE concentration in rats. Corino et al (2002) also observed an increase in serum IgG of piglets Effects of dietary CLA supplementation on weaned pigs 49 due to dietary CLA supplementation. These studies indicated that CLA had positive modulatory impact on the humoral immune response.…”
Section: Discussionmentioning
confidence: 73%
“…An increase in the level of lysozyme in sows and piglets receiving CLA was another observed physiological eff ect of this fatty acid. Lysozyme, which is present in secretions and leucocytes, is very effi cient against gram-positive bacteria (Corino et al, 2002). Weber et al (2001) reported that a supplement of CLA increased the level of serum antibodies against bacteria of the species Mycoplasma hyopnemoniae.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Bontempo et al [ 24 ] and Corino et al [ 13 ] reported that 0.5% CLA supplementation to sows during lactation had no effect on NEFA levels. Corino et al [ 18 ] also observed no difference in NEFA concentration with increasing amount of CLA, whereas triacylglycerol levels markedly decreased in rabbits. On the other hand, Ostrowska et al [ 40 ] found that dietary CLA treatment significantly increased plasma NEFA and triacylglycerol levels in pigs, with no effect on plasma glucose and insulin levels.…”
Section: Discussionmentioning
confidence: 98%
“…As these results are contradictory, further research is needed to elucidate the effects of dietary CLA on milk yield and body weight changes in lactating sows. Regarding immunity in piglets, Corino et al [ 13 , 18 ] found that increasing levels of CLA fed to sows or weaned piglets markedly increased the immunoglobulin G (IgG) concentrations of piglets during suckling and post-weaning. Therefore, transfer of CLA from sows to milk could reduce mortality in piglets by increasing immunity.…”
Section: Introductionmentioning
confidence: 99%